Congenital Posterior Urethral Diverticulum in a Male Child Case Report - Hasan, Zaheer; Kumar, Bindey; Kumar, Prem (Journal of Nepal Paediatric Society, 2013)
Bladder neck and posterior urethra are common sites for obstructive uropathy in children. Diverticula of posterior urethra are rare cause of obstruction in children. A six year old boy presented with features of bladder outflow obstruction since birth. Ultrasound findings were suggestive of posterior urethral valve. Micturating cystourethrogram and endoscopic examinations revealed posterior urethral diverticulum which was placed dorsally. Diverticulectomy and reconstruction of urethra was performed by midline perineal incision. This report emphasizes that a posterior urethral diverticulum may be considered in those cases where features are suggestive of posterior urethral valve bladder outflow obstruction. DOI: http://dx.doi.org/10.3126/jnps.v32i3.5914 J. Nepal Paediatr. SocVol.32(3) 2012 257-258